Splenic marginal zone lymphoma: a population-based study on the 2001–2008 incidence and survival in the United States. Issue 7 (1st July 2013) - Liu, Lihua; Wang, Haijun; Chen, Yiming; Rustveld, Luis; Liu, Gengxin; Du, Xianglin L.
Abstract: The epidemiology of splenic marginal zone lymphoma (SMZL) in the United States has not been addressed. Eight years of data (2001–2008) from 17 registries of the Surveillance, Epidemiology and End Results (SEER) program were used for this study. Of the 116 411 cases of non-Hodgkin lymphoma (NHL) in the registries, 763 (0.6%) were SMZL. The overall annual age-adjusted incidence was 0.13 per 100 000 persons per year. The annual percent change in age-adjusted incidence was 4.81% overall ( p < 0.05), and significantly increasing trends were found for patients who were white, male or aged 70 years and older ( p < 0.05). The relative 5-year overall survival rate for patients with SMZL was 81% (95% confidence interval 75–86%). The incidence of SMZL was highest among whites, males and older patients. A steadily increasing trend in incidence was observed for SMZL. The relative 5-year overall survival rate was high.